Efektivitas Pemberantasan Terhadap Kejahatan Transnasional Pada Masa Globalisasi - Dirgo Hafiizh Danil; Thalita Audrey Azalia; M. Fadhil Andrean (GLOBAL SCIENTS PUBLISHER, 2026)
The current era of globalization has accelerated the movement of information, capital, and people across national borders, while facilitating the emergence of transnational terrorism that threatens national sovereignty and security. In Indonesia, this threat is increasingly apparent with terrorist networks such as Jemaah Islamiyah and ISIS affiliates utilizing digital technology for radicalization and funding. This study analyzes strategies for eradicating transnational terrorism through a normative juridical approach, focusing on the national legal framework (Law No. 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism) as well as international UNSCR 1373/2001 and the ASEAN Convention on Counter-Terrorism. The implication for Indonesia is the need to reform regulations to accommodate aspects of cyber terrorism and strengthen the role of the National Counterterrorism Agency (BNPT) in multilateral forums. This study also recommends a regional cooperation model based on restorative justice with the aim of minimizing re-radicalization, thereby maintaining stability in Southeast Asia.